"Fibrous nests" in human hepatocellular carcinoma express a Wnt-induced gene signature associated with poor clinical outcome. (December 2016) - Désert, Romain; Mebarki, Sihem; Desille, Mireille; Sicard, Marie; Lavergne, Elise; Renaud, Stéphanie; Bergeat, Damien; Sulpice, Laurent; Perret, Christine; Turlin, Bruno; Clément, Bruno; Musso, Orlando
Graphical abstract: "Fibrous nests" : HCCs containing fibrous nests are enriched in Wnt signals. These are associated with markers of mesenchymal commitment, stem cells and extracellular matrix remodeling, indicating tumor aggressiveness. By random forest survival analysis, we show a minimal gene signature (DKK1, COL4A1, LAMC1, SFRP1) associated with poor clinical outcome. By in vitro experiments, we confirm that Wnt signals induce the expression of this minimal gene signature, as well as mesenchymal commitment of liver cancer stem/progenitor cells. Highlights: Fibrous nests contain myofibroblast activation and cancer stem/progenitor cell markers. Cancers carrying fibrous nests express a minimal signature associated with advanced tumor stage and bad clinical outcome. Wnt signals induce the minimal "fibrous nest signature" in liver cancer stem/progenitor cells in vitro. Wnt signals lead to mesenchymal commitment of liver cancer stem/progenitor cells in vitro. Abstract: Hepatocellular carcinoma (HCC) is the 3rd cause of cancer-related death worldwide. Most cases arise in a background of chronic inflammation, extracellular matrix (ECM) remodeling, severe fibrosis and stem/progenitor cell amplification. Although HCCs are soft cellular tumors, they may contain fibrous nests within the tumor mass. Thus, the aim of this study was to explore cancer cell phenotypes in fibrous nests. Combined anatomic pathology, tissue microarray and real-time PCR analyses revealed that HCCs (n = 82) containing fibrous nests were poorly differentiated, expressed Wnt pathway components and target genes, as well as markers of stem/progenitor cells, such as CD44, LGR5 and SOX9. Consistently, in severe liver fibroses (n = 66) and in HCCs containing fibrous nests, weighted correlation analysis revealed a gene network including the myofibroblast marker ACTA2, the basement membrane components COL4A1 and LAMC1, the Wnt pathway members FZD1; FZD7; WNT2; LEF1; DKK1 and the Secreted Frizzled Related Proteins (SFRPs) 1; 2 and 5. Moreover, unbiased random survival forest analysis of a transcriptomic dataset of 247 HCC patients revealed high DKK1, COL4A1, SFRP1 and LAMC1 to be associated with advanced tumor staging as well as with bad overall and disease-free survival. In vitro, these genes were upregulated in liver cancer stem/progenitor cells upon Wnt-induced mesenchymal commitment and myofibroblast differentiation. In conclusion, fibrous nests express Wnt target genes, as well as markers of cancer stem cells and mesenchymal commitment. Fibrous nests embody the specific microenvironment of the cancer stem cell niche and can be detected by routine anatomic pathology analyses.